2023
DOI: 10.1007/s00432-023-04587-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of baseline and early response FDG-PET/CT in patients with refractory and relapsed aggressive B-cell lymphoma undergoing CAR-T cell therapy

Abstract: Purpose Chimeric antigen receptor (CAR)-T cells are a viable treatment option for patients with relapsed or refractory (r/r) aggressive B-cell lymphomas. The prognosis of patients who relapse after CAR-T cell treatment is dismal and factors predicting outcomes need to be identified. Our aim was to assess the value of FDG-PET/CT in terms of predicting patient outcomes. Methods Twenty-two patients with r/r B-cell lymphoma who received CAR-T cell treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
3
1
0
Order By: Relevance
“…An early relapse at month 1 following CAR-T infusion detected by PET-CT was associated with a very poor prognosis whereas a complete metabolic remission at month 3 was linked to a favorable survival outcome. These findings, consistent with others, provide a rationale for early PET-CT to predict responses and in the event of progression or relapse, alternative treatments should be applied (Kuhnl et al 2022 ; Georgi et al 2023 ).…”
Section: Discussionsupporting
confidence: 83%
“…An early relapse at month 1 following CAR-T infusion detected by PET-CT was associated with a very poor prognosis whereas a complete metabolic remission at month 3 was linked to a favorable survival outcome. These findings, consistent with others, provide a rationale for early PET-CT to predict responses and in the event of progression or relapse, alternative treatments should be applied (Kuhnl et al 2022 ; Georgi et al 2023 ).…”
Section: Discussionsupporting
confidence: 83%
“…An early relapse at month 1 following CAR-T infusion detected by PET-CT was associated with a very poor prognosis whereas a complete metabolic remission at month 3 was linked to a favorable survival outcome. These ndings, consistent with others, provide a rationale for early PET-CT to predict responses and in the event of progression or relapse, alternative treatments should be applied [34,35].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we demonstrate that patients with DS ≤ 4 prior CAR T-cell therapy tend towards longer PFS compared to patients with a pretherapeutic DS 5. In line with that, Georgi et al demonstrated, that patients with CMR (DS ≤ 3) on pre-therapeutic FDG-PET/CT had better PFS and tend to had better OS compared to patients with non-CMR (DS > 3) on pre-therapeutic FDG-PET/CT [29]. Further studies are needed to clarify whether a DS ≤ 4 on pre-therapeutic FDG-PET/CT may be used as a valid response predictor prior to therapy.…”
Section: Discussionsupporting
confidence: 55%